The Role of SWOT in Business Analysis for Enhancing Competitive Advantage at The Kundasang Aquafarm - Heru Fachrezie; Aiyshah Izaty binti Roslan; Abel Gandhy; Ing Grace Phang (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This research focuses on developing agribusiness strategies for aquaponic systems. This research aims to provide recommendations for business strategies that drive improved performance and business development. The aquaponic agribusiness at Kundasang Aquafarm allows for significant growth. A business strategy provides a long-term plan to manage resources comprehensively, while identifying opportunities that support future business success and achieve optimal levels of profitability. This research was conducted at Kundasang Aquafarm, Kota Kinabalu, which was purposively selected because the aquaponics activity has room for potential development and encourages greater growth. This study used quantitative and qualitative data sourced from primary and secondary data. Primary data was collected through surveys and direct observation by the researcher, while secondary data was obtained from institutional reports, journals, books, news articles, and other literature sources. An internal (IFE) and external (EFE) environmental analysis was conducted to identify factors that could affect business success. The results of this analysis were used in the Internal-External (IE) Matrix which resulted in three main strategies: Growth, Stability, and Reduction strategies. These strategies form the basis of Kundasang Aquafarm's agribusiness development.